(untitled) (World Economics and Finance Bulletin, 2023)
This research aims to identify the impact of green human resources management in its dimensions Green Employment, Green Training, Green Performance Assessment, Reward and Green Pay Systems to enhance the staff capacity of a sample of Samarra General Hospital staff, and to achieve the research objectives, a form prepared for this purpose has been designed after presentation to some professors of specialization to give them consistency and validation, which has been distributed to a sample of hospital staff managers (60), 58 valid forms have been recovered and after the use of the statistical package program (Spss) The necessary statistical analysis was carried out as the study reached a set of conclusions, the most important of which The existence of a very strong correlation between the dimensions of green human resource management, with a strong correlation, whether among themselves or on the total sum of its dimensions, as the correlation coefficient for the dimensions ranged between (0.871-1) at the level of significance (0.01), which indicates the existence of a close and significant correlation between the variables above and that it has a strong (directive) effect on green human resource management, and thus the influence hypothesis that there is an effect of green human resource management on enhancing the capabilities of employees in the hospital under study has been proven. It leads to improving their performance and practice towards green environmental work